2004
DOI: 10.1038/sj.bjp.0705710
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effect of diosmectite in hapten‐induced colitis in the rat

Abstract: 1 Diosmectite is a natural silicate effectively used in the treatment of infectious diarrhoea. Its antidiarrhoeal properties involve adsorption of toxins and bacteria and modifications of the rheological characteristics of gastrointestinal mucus. Hence, the aim of this study was to test the intestinal anti-inflammatory activity of diosmectite. 2 Diosmectite (500 mg kg À1 day À1 , p.o.) was administered as a post-treatment to rats with chronic trinitrobenzene sulphonic acid colitis. Colonic status was checked 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 38 publications
3
79
1
3
Order By: Relevance
“…In contrast, diosmectite, which does not affect AP, has little impact on colonic glutathione levels. 52 Hence, we hypothesized that oxidative stress might be the causative factor of the AP increase. Our data clearly support this hypothesis since AP is increased in several cell lines of intestinal epithelial phenotype with different oxidative stimuli, including monochloramine, which is produced in high amounts in inflammatory foci as a byproduct of the reaction of myeloperoxidase derived hypochlorous acid with amines, 45 and tButOOH, which was used here to evoke lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, diosmectite, which does not affect AP, has little impact on colonic glutathione levels. 52 Hence, we hypothesized that oxidative stress might be the causative factor of the AP increase. Our data clearly support this hypothesis since AP is increased in several cell lines of intestinal epithelial phenotype with different oxidative stimuli, including monochloramine, which is produced in high amounts in inflammatory foci as a byproduct of the reaction of myeloperoxidase derived hypochlorous acid with amines, 45 and tButOOH, which was used here to evoke lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…18-20, 61 They have also been shown to adhere to and reinforce the intestinal mucin layer, 64,65 another possible mechanism for protection. An in vivo study of the pathogen and toxin binding capacity of geophagic and amylophagic substances would be highly useful in understanding this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Diosmectite has demonstrated significant anti-inflammatory activity in an experimental rat model of hapten-induced colitis. [27] Furthermore, the level of anti-inflammatory action was comparable to that of established treatments such as sulfasalazine. Possible anti-inflammatory mechanisms include adsorption of luminal antigens produced during the inflammation process, an increase in colonic mucin levels, and modulation of cytokine production by mucosal cells; several effects on proinflammatory cytokines have been demonstrated that contribute to the anti-inflammatory effects of diosmectite (see section 4.4).…”
Section: Anti-inflammatory Activitymentioning
confidence: 84%